Comparison of the companies based on the composite sustainable development index and the method of the hierarchichal analysis - Климюк, Ольга Олексіївна; Безносик, Юрій Олександрович (Eastern-European Journal of Enterprise Technologies, 2012)
This paper presents a model for designing a composite sustainable development index that depicts performance of companies along all the three dimensions of sustainability—economic, environmental, and societal